Sunday Express (16 May 1926) - Kelleway, C. E., 1886-1944 ; Douglas, James, 1867-1940 ; Gardiner, A. G. (Alfred George), 1865-1946 ; Swaffer, Hannen, 1879-1962 ; Page, Philip ; Atkinson, G. A. ; Morse-Boycott, Desmond ; Hicks, Cranfield
16 May 1926